Study of nucleation and growth mechanism of the metallic nanodumbbells - Krylova, Galyna (2012)
We propose a general nucleation and growth model that can explain the mechanism of the formation of CoPt 3/Au, FePt/Au, and Pt/Au nanodumbbells. Thus, we found that the nucleation event occurs as a result of reduction of Au + ions by partially oxidized surface Pt atoms. In cases when Au 3+ is used as a gold precursor, the surface of seeds should be terminated by ions (e.g., Co 2+, Pb 2+) that can reduce Au 3+ to Au + ions, which can further participate in the nucleation of gold domain. Further growth of gold domain is a result of reduction of both Au 3+ and Au + by HDA at the surface of gold nuclei. We explain the different ability of CoPt 3, Pt, and FePt seeds to serve as a nucleation center for the reduction of gold and further growth of dumbbells. We report that the efficiency and reproducibility of the formation of CoPt 3/Au, FePt/Au, and Pt/Au dumbbells can be optimized by the concentration and oxidation states of the surface ions on metallic nanocrystals used as seeds as well as by the type of the gold precursor.